Efficient and High‐Speed Transduction of an Antibody into Living Cells Using a Multifunctional Nanocarrier System to Control Intracellular Trafficking. Issue 9 (26th December 2014) - Yamada, Yuma; Perez, Sandra Milena Vergara; Tabata, Mai; Abe, Jiro; Yasuzaki, Yukari; Harashima, Hideyoshi; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> The transduction of antibodies into living cells would represent a major contribution to both basic and applied biomedical fields, as currently available methods suffer from limitations such as low‐uptake efficiency and endosomal entrapment. In this study, a liposome‐based carrier was designed to overcome these issues. Liposomes were modified with octaarginine (R8), a cell penetrating peptide and GALA, a pH‐sensitive fusogenic peptide. The presence of R8 enhanced the cellular uptake of antibodies, whereas GALA reduced endosomal entrapment, resulting in antibodies being released into the cytosol within 30 min. Moreover, compared with commercially available reagents for delivering antibodies, our system was superior in both cellular uptake and endosomal escape. In addition, specific antibodies delivered by R8‐GALA liposomes were found to be associated with their epitope, confirming the preservation of functionality. This system for the efficient and high‐speed cytosolic delivery of an antibody provides a valuable tool that can be useful in basic and applied research for analyzing the expression and function of intracellular molecules. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2845–2854, 2015